2009
DOI: 10.1542/peds.2008-2583
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in 1- to 3-Month-Old Infants: Ambulatory Treatment With Intravenous Antibiotics

Abstract: Ambulatory treatment of infants 30 to 90 days of age with febrile urinary tract infections by using short-term, intravenous antibiotic therapy at a day treatment center is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 28 publications
2
18
3
Order By: Relevance
“…E.coli (27.05%) was the commonest organism isolated in both sex (male) from UTI cases in this study. Second most common isolates was klebsiella which was well correlating to other study [18][19][20] Prevalence of E.coli and Klebsiella was high in girls; similar result was reported by study conducted bySpahiuL in 2010 [19] Although E. coli, Klebsiella were the principal uropathogens in our study, there were other pathogens of our interest due to their resistance pattern like, Pseudomonas, Proteus, Staphylococcus, Acinetobacter and Enterobacter. Resistance in these pathogen was as high as E.coli and klebsiella.…”
Section: Discussionsupporting
confidence: 91%
“…E.coli (27.05%) was the commonest organism isolated in both sex (male) from UTI cases in this study. Second most common isolates was klebsiella which was well correlating to other study [18][19][20] Prevalence of E.coli and Klebsiella was high in girls; similar result was reported by study conducted bySpahiuL in 2010 [19] Although E. coli, Klebsiella were the principal uropathogens in our study, there were other pathogens of our interest due to their resistance pattern like, Pseudomonas, Proteus, Staphylococcus, Acinetobacter and Enterobacter. Resistance in these pathogen was as high as E.coli and klebsiella.…”
Section: Discussionsupporting
confidence: 91%
“…The wide range in occurrence of bacteremia may be explained by the different numbers and age ranges of children included in these studies. 5,7,8,[11][12][13][14][15][16]19,35 Several studies have reported the benign course of UTI in infants, even when accompanied by bacteremia, although the bacteremia rate was low in these studies, 4-9 making comparison between bacteremic and nonbacteremic episodes problematic. 11,13,35,36 The course of illness was relatively benign in the children in our study too, except for longer time to defervescence in the bacteremic children.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several retrospective studies reported that bacteremic children with UTI (age range from 0 to 18 years) were provided with longer parenteral therapy when compared with nonbacteremic. 36,37 Whether all febrile infants <1 month of age will be usually hospitalized and receive parenteral therapy, in centers which consider oral therapy in the older infants, identification of those at high risk for bacteremia may help to focus the parenteral treatment and inpatient observation on these specific infants; impaired renal function provides another clue to the decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Montreal in Canada reported on the feasibility of ambulatory treatment in this group using short-term i.v. antibiotic therapy at a day treatment center [49 ]. Zaoutis et al…”
Section: Key Articlesmentioning
confidence: 99%